If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 4n = 2 Solving 6 + 4n = 2 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 4n = 2 + -6 Combine like terms: 6 + -6 = 0 0 + 4n = 2 + -6 4n = 2 + -6 Combine like terms: 2 + -6 = -4 4n = -4 Divide each side by '4'. n = -1 Simplifying n = -1
| T^2+23t+90=0 | | 2b^2+5b-12=0 | | 4=x+14 | | 12b^2-7b+1=0 | | 4=x+10 | | x-18=3x | | 4(x+2y)= | | n-8(1+n)=-4n-32 | | -3y+12=-2(3y+6) | | 4x+3=c | | 5((-8-3y)-2)-2y=-1 | | n-8(1+n)=-4-32 | | y=6x-x^2-8 | | 3b^2-16b+5=0 | | 2x^3+14x^2+24x= | | 2b^2-b-10=0 | | -(y+12)=4 | | 21-5=4 | | 0.8x+4=12 | | -9(t-4)-(t+5)=3 | | 3b^2-13b+4=0 | | 3x^6y^4+27x^4y^3+15xy= | | -9+3k=6(k+2) | | 8+6y=0 | | 4x/3+4=12 | | 9x^7-45x^5= | | 2b^2-11b+5=0 | | 4+3y=9 | | 7(x+3)-3(4x+9)=14 | | 7p+12=12+13p | | ax+2=b | | 2b^2-13b+4=0 |